Prevalence and risk factors associated with prehypertension and hypertension among attendants of patients at a rural tertiary care institute of Haryana - Rani, Babita; Pal, Ravinder; Jha, S. K.; Punia, Anita; Singh, Sanjeet; ., Tarun (International Journal Of Community Medicine And Public Health, 2019)
Background: Hypertension (HTN) is the leading risk factor for death and disability globally and disproportionately impacts low-and middle-income countries. HTN is present in 25% of urban and 10% of rural subjects in India. Our objective was to estimate the prevalence of pre-HTN and HTN among the attendants of patients at a rural tertiary care institute of Haryana. Methods: This was a hospital-based cross-sectional study. A total of 309 attendants of patients were enrolled for this study. Diagnosis of pre-HTN and HTN was done on the basis of seventh joined national committee guidelines. Data were collected on a semi-structured proforma and were analysed by using R software. Results: The prevalence of pre-HTN and HTN was 18.4% and 21.4% respectively. Both the pre-HTN and HTN were significantly higher in males (p=0.002) and in the age group of 45 to 55 years (p<0.001). The multinomial logistic regression analysis revealed that sex, age >55 years and BMI >23 kg/m2 were significantly associated with pre-HTN and HTN. Conclusions: The prevalence of both prehypertension and hypertension is high in rural Haryana. This makes the people of this area vulnerable to several chronic diseases. The ﬁndings warrant urgent measures to lower the risk factors in rural communities. So, programs are needed to improve the surveillance systems and implementation of community based screening programs for early detection of hypertension.